Tackling Labour Mismatches and Promoting Mobility in Hungary - Sorbe, Stéphane (OECD Publishing, 2014)
Significant labour market mismatches and insufficient mobility penalise employment and productivity. Mismatches have above all a skills dimension, with an excess of low-skilled workers and a possible lack of skilled workers in certain domains. Reducing the high tax wedge on low salaries and avoiding excessive minimum wage increases would support demand for low-skilled labour. In the longer term, upgrading the labour supply requires improving educational outcomes, especially of disadvantaged students, and making the school-to-work transition less abrupt. To facilitate good matching and enhance sectoral mobility, a somewhat longer duration of unemployment benefits and an upscaled Public Employment Service would be of value, as well as greater focus on reintegration in the public works programme and more efficient and developed lifelong learning. Besides skills mismatches, important geographic mismatches are illustrated by high and persistent regional disparities in the unemployment rate. Mobility is hampered by the underdevelopment of the rental housing market, while there is room to enhance the efficiency of public transport to further support commuting
Keywords: Employment; Economics; Hungary